Effect of Replacement of Fish Meal by Soybean Meal on Growth of Oreochromis niloticus (Linné, 1758) Juvenile under High Temperature Treatment for Masculinization - Boussou, Charles Koffi; Aliko, Gustave Nguessan; Yoboué, Nicole Ahou; Konan, Félix Koffi; Ouattara, Mamadou; Gourène, Germain (International Journal of Applied Sciences and Biotechnology, 2017)
Two experiments were conducted consecutively in triplicates to evaluate and compare the impact of different feeds on survival rate and growth performances of Oreochromis niloticus larvae during both the heat treatment for thermal masculinization and the subsequent juvenile stage. A commercial feed containing fishmeal with 32.38% crude protein (CFA) and an experimental feed with 25.48% crude protein (EFB) where fish-meal was entirely replaced by soybean meal were tested. In the first experiment, larvae of about 4 days post-hatch were reared for 21 days at a temperature of 36°C and the second has consisted in testing at ambient temperature the performances of these feeds on the previous fry for 70-72 days. Fish were fed four times a day ad libitum. Results showed that there were no significant differences between growth performances (survival rate, final body weight, daily weight gain and specific growth rate) of larvae bred in hot water and nourished with feed containing fishmeal (CFA) or feed containing soybean (EFB) as protein source. However, better results were obtained with control batches bred at ambient temperature and fed with feed CFA or EFB. Post-larval rearing of previously heated fry showed that feed containing fishmeal has similar growth performances as feed containing soybean. Then, soybean meal can replace successfully fish-meal in diet of larvae during heating treatment for masculinization and also for the post-larval rearing of fry. Int. J. Appl. Sci. Biotechnol. Vol 5(1): 30-36